Gestion et traduction : Un mariage de raison - Fillion, Laurent (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1984)
AbstractThis informative article entitled "Management and Translation : A Marriage of Convenience" describes how, in the day to day operations of the Translation Bureau as well as its future-oriented activities, management and translation have, over the years, formed an indissociable bond. Five fields - contracting services, terminology and documentation, recruitment and training, office automation and computer translation - are examined in some depth. Those wishing to obtain an English version of this article or more information should contact the author at the Planning, Management and Technology Branch, Translation Bureau, Secretary of State Department, Ottawa, Ontario, K1A OM5.